2019
DOI: 10.1186/s11671-019-3053-4
|View full text |Cite
|
Sign up to set email alerts
|

Her2-Functionalized Gold-Nanoshelled Magnetic Hybrid Nanoparticles: a Theranostic Agent for Dual-Modal Imaging and Photothermal Therapy of Breast Cancer

Abstract: Targeted theranostic platform that integrates multi-modal imaging and therapeutic function is emerging as a promising strategy for earlier detection and precise treatment of cancer. Herein, we designed targeted gold-nanoshelled poly (lactic-co-glycolic acid) (PLGA) magnetic hybrid nanoparticles carrying anti-human epidermal growth factor receptor 2 (Her2) antibodies (Her2-GPH NPs) for dual-modal ultrasound (US)/magnetic resonance (MR) imaging and photothermal therapy of breast cancer. The agent was fabricated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…SKBR3 cells in competition group no longer showed distinctly fluorescence signals, which confirmed receptor-mediated targeting binding of Her2-GPH NCs and could be blocked by excess free anti-Her2 antibodies. 40 In addition, there was little fluorescence in MDA-MB-231 cells incubated with Her2-GPDH NCs (d), which confirmed the targeting specifically of Her2-GPDH NCs to Her2positive SKBR3 cells.…”
Section: Dox Loading and Releasementioning
confidence: 76%
“…SKBR3 cells in competition group no longer showed distinctly fluorescence signals, which confirmed receptor-mediated targeting binding of Her2-GPH NCs and could be blocked by excess free anti-Her2 antibodies. 40 In addition, there was little fluorescence in MDA-MB-231 cells incubated with Her2-GPDH NCs (d), which confirmed the targeting specifically of Her2-GPDH NCs to Her2positive SKBR3 cells.…”
Section: Dox Loading and Releasementioning
confidence: 76%
“…Similarly, gold has been widely used in cancer treatment. 38 , 47 , 48 Compared with chemotherapy, photothermal effect mediated by gold has the advantage of repeatable treatment in a short time period with low toxicity and does not lead to drug resistance. In addition, studies 19 , 20 show that photothermal therapy can remodel the tumor microenvironment by decreasing the number of CAFs in the tumor, and enhance the accumulation of nanomedicine after the stroma decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of Her2-DOX-SPIOs @PLGA@Au NPs Her2-DOX-SPIOs@PLGA@Au (Her2-DSG NPs) were prepared according to the previous report from our research group. 37,38 DOX-SPIOs@PLGA nanoparticles (DS NPs) were prepared using the single emulsion oil-inwater (O/W) solvent evaporation method. Hydrochloric acid doxorubicin (10 mg) reacted with triethylamine (20 μL) was transformed to oil phase from water phase.…”
mentioning
confidence: 99%
“…Previously, several studies reported the enhanced accumulation of functionalized tumor-targeted nanoparticles as compared to non-coated particles. 16,69,70 The effect of tumor targeting on biodistribution both biologically and mathematically will hence be the next important step in further studies, since ways to make intravenous injections viable may be a crucial part of making nanoparticle-based agents viable for clinical application.…”
Section: Discussionmentioning
confidence: 99%